2021
DOI: 10.1002/anie.202102313
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Catalytic Benzylic C−H Oxidation over a Redox‐Active Metal–Organic Framework

Abstract: Selective oxidation of benzylic CÀH compounds to ketones is important for the production of a wide range of fine chemicals, and is often achieved using toxic or precious metal catalysts. Herein, we report the efficient oxidation of benzylic C À H groups in a broad range of substrates under mild conditions over a robust metal-organic framework material, MFM-170, incorporating redox-active [Cu 2 II (O 2 CR) 4 ] paddlewheel nodes. A comprehensive investigation employing electron paramagnetic resonance (EPR) spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 37 publications
(60 reference statements)
1
18
0
Order By: Relevance
“…of moles of catalyst used)/reaction time). 40 Under the optimal conditions, 1 catalyzed indane to 1-indanone with a conversion of above 99% and selectivity of 97%, while the blank experiment without any catalyst only reached a low conversion of 35% (Fig. 2a).…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…of moles of catalyst used)/reaction time). 40 Under the optimal conditions, 1 catalyzed indane to 1-indanone with a conversion of above 99% and selectivity of 97%, while the blank experiment without any catalyst only reached a low conversion of 35% (Fig. 2a).…”
Section: Resultsmentioning
confidence: 92%
“…Considering the constituent and structural features of 1 and the related studies reported in the literature, 40,61 we analyze the possible generation pathways of t BuO˙ and t BuOO˙ during the oxidation process of benzylic compounds catalyzed by 1 . Generally, the catalytic site of Cu I is favorable for triggering the formation of the t BuO˙ radical, while both high-valence {V 4 } and Cu II are prone to triggering the formation of the t BuOO˙ radical.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations